Folivory and seasonal changes in diet in Rana hexadactyla (Anura: Ranidae) - Das, Indraneil (The Zoological Society of London, 1996)
The autecology of Rana hexadactyla (Lesson) was studied at a seasonal locality in south India. The herbivorous larva transforms into an insectivorous frog, and a second dietary switch from insectivory to folivory occurs in adults, with plants constituting 79.5% of the diet, by volume. A variety of invertebrates and small vertebrates is consumed, especially by the adult females before the reproductive season. Larger frogs take larger animal prey and more prey types. Monthly figures of prey diversity generally show high values during the wet months.